Ratings, Commercial Paper, and Equity Returns - NAYAR, NANDKUMAR; ROZEFF, MICHAEL S. (Journal of Finance, 1994)
ABSTRACT We present the first evidence that initial ratings of commercial paper influence common stock returns. Highly‐rated industrial issues of commercial paper, unaccompanied by bank letters of credit, are associated with significantly positive abnormal returns; lower‐rated issues are not. The stock price effects of changes in commercial paper ratings also demonstrate the relevance of ratings to the financing of firms. Rating downgrades, especially those that imply an exit from the commercial paper market, produce significantly negative abnormal returns; upgrades have no effects. Initial commercial paper ratings and subsequent reratings appear to help investors sort firms by their future prospects.